Listen and win communicate for a competitive edge - Kratz, Dennis M.; Kratz, Abby Robinson (Jack Wilson and Associates, 1990)
In this training program you will learn the basics of listening, how to tailor your listening skills to various situations, how to give and get good feedback and why it's important, how to identify "communication noise" and get rid of it, why taking notes helps you become a better listener, how to ask the proper questions and be able to listen and remember the answers, what is important in what a speaker is saying, how to listen to learn, decide and enable.